Enhanced removal of tetracycline over CeMO-7 % nanorods via electronic interaction effect: Degradation, kinetics and mechanism. (December 2022) - Fang, Chen; Huang, Yingping; Wang, Yanlan; Meng, Xu; Wang, Xiaopei; Liu, Xiang
Abstract: Although multifarious strategies, including oxygen vacancies or surface defects improvement, morphology modification, crystal phase transition and ion doping, have been developed for improving the catalytic performance of MnO2 in the removal of pollutant substances. As far as we know, there is the first report providing enhanced performance of MnO2 in the removal of pollutant substances by its electronic interaction effect. Herein, this study proposes a facile and high-efficiency method to achieve Ce-doping manganese oxide (CeMO) nanorods for the enhanced tetracycline removal via electronic interaction effect at 30 °C for the first time. The detailed characterizations and anions effect experiment have confirmed that CeMO-7 % nanorods possessed abundant surface reactive oxygen species, which is in favor of PMS activation. Compared to manganese oxide (MO), CeMO-5 % and CeMO-9 %, an obvious left shift has been observed in the Mn 2p of CeMO-7 %, suggesting that some electrons are transferred from Mn atoms to Ce atoms in CeMO-7 %, and implying that the highest degradation efficiency of CeMO-7 % in TC degradation may be due to the strong electronic interaction between Ce and Mn in CeMO-7 %. This study not only offers a facile and high-efficiency methodology for the synthesis of two-dimensional nanomaterial, but also proposes a new idea for enhancing the removal of TC. Graphical abstract: Unlabelled Image Highlights: CeMOs are prepared by the pre -incorporation method from KMnO4, MnSO4 and Ce(NO3 )3 . CeMO-7 % is found to be an efficient catalyst for TC removal via PMS activation. Enhanced degradation of TC over CeMO-7 % by electronic Interaction effect This work provides a new idea for enhancing the removal of TC.